Preliminary evaluation of impacts from science-technologies to economic development of Red River Delta area - Tuan, Tran Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The paper has targets to evaluate impacts from science and technology (S&T) to economic development of Red River Delta area through interactive relations between indicators reflecting S&T activities. The evaluation is based on integrated approaches and selections of related factors. Particularly in this paper, the research team conducted the separate evaluations of S&T factors from many other factors. By using iterative functions for identification of these relations, the study helps to identify the rate of impacts from these factors and then to identify orientations to adjust them in order to enhance the effectiveness of economic development.